2012
DOI: 10.1186/1472-6882-12-164
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and patterns of prenatal use of traditional medicine among women at selected harare clinics: a cross-sectional study

Abstract: BackgroundPrenatal use of traditional medicine or complementary and alternative medicine is widespread globally despite the lack of evidence of the effectiveness of these therapeutic options. Documentation on the prevalence and patterns of this maternal practice in the Zimbabwean setting was also lacking.MethodsA cross sectional survey of 248 women at selected health centres in Harare was carried out to address the need for such data using an interviewer-administered questionnaire.ResultsFifty-two (52%) (95% C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
30
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 9 publications
5
30
1
Order By: Relevance
“…Some women reported that the use of traditional and complementary medicine was associated with the perception that it increases immunity. Similarly, traditional medicine was often perceived as a better preventive strategy and regarded as more natural, safe, and/or having at least equal efficacy when compared with medical prescriptions for maternal wellbeing among African women in Africa [42,43]. As such, the present finding may suggest that previous perceptions among African migrant women were important to continued us of traditional medicine because they believed that it has a medicinal value which was important to protect their general wellbeing.…”
Section: Discussionmentioning
confidence: 70%
“…Some women reported that the use of traditional and complementary medicine was associated with the perception that it increases immunity. Similarly, traditional medicine was often perceived as a better preventive strategy and regarded as more natural, safe, and/or having at least equal efficacy when compared with medical prescriptions for maternal wellbeing among African women in Africa [42,43]. As such, the present finding may suggest that previous perceptions among African migrant women were important to continued us of traditional medicine because they believed that it has a medicinal value which was important to protect their general wellbeing.…”
Section: Discussionmentioning
confidence: 70%
“…This is relatively low compared with other similar studies in Sub-saharan Africa-12% in Kenya in a district hospital 14 ; 50.4% in Ethiopia 15 and 50.0% in Harere. 16 For this study in Offinso North district, pregnant women were asked open-ended questions to assess whether they used any herbal medicines during pregnancy. Open-ended questions yield lower percentage for answers.…”
Section: Discussionmentioning
confidence: 99%
“…The use of indigenous medicinal plants as a part of antenatal care was common in developing nations, such as in Africa and Asia (Mureyi et al, 2012;Al-Ramahi et al, 2013;Elkhoudri et al, 2016;Maputle et al, 2015;Tang et al, 2016;Onyiapat et al, 2017). Such medicinal plants were typically consumed in a crude form, or as infusions, decoctions, and tinctures.…”
Section: Consumption Of Hms By Pregnant Womenmentioning
confidence: 99%
“…HM was usually used in the first trimester for prevention and/or treatment of early pregnancyrelated issues such as nausea, vomiting, and gastrointestinal disorders. During the third trimester, they were commonly used to prepare the uterus for labor and ease child delivery (Mureyi et al, 2012;Nyeko et al, 2016;Onyiapat et al, 2017). Nonetheless, it was not uncommon for women to use HMs throughout all trimesters of pregnancy, usually with the intent to improve the well-being of the mother and unborn child.…”
Section: Consumption Of Hms By Pregnant Womenmentioning
confidence: 99%